Effect of the eutectic Sn-Cu alloy-to-Cu content ratio on the structure and properties of conductive polyamide-66 composites. (14th September 2016) - Zou, Mingjing; He, Jiangping; Lei, Yajie; Zhang, Fengshun; Zhao, Qi; Liu, Tao; Ma, Hanbing; Yi, Yong
Abstract: Adding a low melting point metal (LMPM) with a high melting point metal (HMPM) into a polymer has been used to prepare highly conductive, melt processable composites, but the effect of the content ratio of the two metals on the composite structure and properties is not clear. In this work, a ternary system composed of eutectic Sn-Cu alloy (ESCA), Cu powder and polyamide-66 (PA66) was used to study the effect of the LMPM-to-HMPM content ratio on the structure and properties of composites. It was found that the ESCA reacted with Cu powder in PA66 to form intermetallic compounds that were in the solid state during processing. For composites with ESCA-to-Cu ratio (VEut /VCu ) < 1.5, all of the added ESCA reacted with Cu and the metal phase was solid during processing. For composites with VEut /VCu > 1.5, only part of the ESCA was consumed by the reaction with Cu, and the metal phase became a suspension of liquid ESCA with solid intermetallic compound. The morphology of metal phase transformed from evenly dispersed, isolated "islands" to physically continuous networks with a relatively large size as VEut /VCu was increased. Consequently, the conductivity, fluidity and toughness of the composites with VEut /VCu ranging from 2 to 3.5 were simultaneously improved with increasing this ratio. These properties of composites with well-developed physically continuous metal networks were even higher than those of composite filled with only Cu powder. Our results also indicate that simultaneously using LMPM and HMPM helps mitigate the deterioration in fluidity and toughness of composites when attempting to enhance the conductivity by increasing the metal content.